2010
DOI: 10.1016/j.brainresbull.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and behavioural effects of acute and chronic memantine administration in rats: Further support for NMDA as a new pharmacological target for the treatment of depression?

Abstract: A growing body of evidence has pointed to the NMDA receptor antagonists as a potential therapeutic target for the treatment of major depression. The present study was aimed to evaluate behavioural and molecular effects of the acute and chronic treatment with memantine and imipramine in rats. To this aim, rats were acutely or chronically for 14 days once a day treated with memantine (5, 10 and 20 mg/kg) and imipramine (10, 20 and 30 mg/kg) and then subjected to the forced swimming and open-field tests. The acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 39 publications
3
60
1
Order By: Relevance
“…On the other hand, new studies have attributed other individual properties to memantine in some disorders, including schizophrenia, bipolar disorder and depression (reviewed in Zdanys and Tampi 2008). Preclinical studies have demonstrated that memantine displays antidepressant-like effects in rats subjected to animal models of depression (Réus et al 2010;Almeida et al 2006;Skuza and Rogóz 2003;Rogóz et al 2002). In fact, our group very recently showed that acute and chronic treatments with memantine reduced immobility time of rats; in addition acute, but not chronic treatment with memantine increased brain-derived-neurotrophic factor (BDNF) protein levels in rat hippocampus (Réus et al 2010).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, new studies have attributed other individual properties to memantine in some disorders, including schizophrenia, bipolar disorder and depression (reviewed in Zdanys and Tampi 2008). Preclinical studies have demonstrated that memantine displays antidepressant-like effects in rats subjected to animal models of depression (Réus et al 2010;Almeida et al 2006;Skuza and Rogóz 2003;Rogóz et al 2002). In fact, our group very recently showed that acute and chronic treatments with memantine reduced immobility time of rats; in addition acute, but not chronic treatment with memantine increased brain-derived-neurotrophic factor (BDNF) protein levels in rat hippocampus (Réus et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In fact, a recent post-mortem study showed an increase in glutamate levels, which may be cytotoxic, in prefrontal cortex of patients with major depression (Hashimoto et al 2007). In addition, antagonists of N-methyl-D-aspartate (NMDA) receptor (such as, ketamine and memantine) have antidepressant effects in animal models of depression and in humans (Réus et al 2010;Chourbaji et al 2008;Feyissa et al 2009;Garcia et al 2008a, b;Phelps et al 2009;Zarate and Manji 2008;Liebrenz et al 2007;Ferguson and Shingleton 2007;Zarate et al 2006;Berman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Increasing evidence suggests that several NMDA receptor antagonists are effective in the treatment of depression. Mem antine, a noncompetitive NMDA receptor antagonist, has produced antidepressant effects in the forced swim test in rats, 12 and CP-101606, an NR2B subunit-selective NMDA receptor antagonist, has been shown to elicit an antidepressant response in depressed patients. 13 These findings suggest that NMDA receptor antagonists could have therapeutic potential for the treatment of major depression.…”
Section: Introductionmentioning
confidence: 99%
“…The glutamatergic system has recently been a target for the development of binge-eating medication [57]. It was shown that memantine (a NMDA antagonist) and MTEP (a mGluR5 antagonist) reduces highly palatable food consumption in rats and baboons [56,60]. Memantine similarly reduced the effect of highly rewarding stimuli (e.g., sexual interaction and morphine intake) in mice [8,56].…”
Section: Discussionmentioning
confidence: 99%